Preventive dentistry in a hospital setting - San Juan, Sofronio P. (The Journal of the Philippine Dental Association)
Oral health care services in a hospital could either be a full department, or as support services for medical management of admitted in-patients. This paper presents the scope of these services that could be made available in a hospital setting. Some categories of patients who are in need of primary, secondary and tertiary preventive dentistry services citing medical-related oral health problems will be discussed. These will include several side effects of cancer therapy, handicapped, maternal, infant and child care, as well as medically compromised patients.